The complete chloroplast genome sequence of Disanthus cercidifolius Subsp. Longipes (Hamamelidaceae). Issue 1 (2nd January 2019) - Yu, Jiaojun; Hu, Guoxiong; Zhao, Fei; Dong, Hongjin
Abstract: Disanthus cercidifolius Maximowicz subsp. longipes (H. T. Chang) K. Y. Pan is a rare and Endangered species endemic to central China. Here, we assembled and annotated the complete chloroplast (cp) genome. It is 158, 148 bp in length and encodes 87 protein-coding genes, 37 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. This chloroplast genome sequencing offers a useful resource for future conservation genetics and phylogenetic studies.